Pengaruh Strategi Lean Management Terhadap Efisiensi Pengelolaan Obat Di Instalasi Farmasi Rumah Sakit - Edi Pramono; Arifina Fahamsya; Achmad Indra Awaluddin; Sara Surya; Rahmat Pannyiwi (Barongko: Jurnal Ilmu Kesehatan, 2026)
Background: Efficient medication management is a critical factor in hospital pharmacy services. Many hospitals face challenges in controlling medication inventory, service times, and operational costs. Lean Management strategies offer an approach to increasing efficiency by eliminating waste, improving workflows, and optimizing resources. Objective: This study aims to analyze the effect of implementing a Lean Management strategy on medication management efficiency in a hospital pharmacy. Methods: This study used a quasi-experimental design with a pre-test and post-test approach. The sample consisted of the pharmacy department of one hospital implementing Lean Management, with efficiency measurements taken before and after the strategy implementation. Data were analyzed using a paired t-test to compare average medication management time, dead stock levels, and operational costs. Results: The implementation of Lean Management was proven to reduce the average medication management time from 12.5 hours to 8.2 hours per batch (p < 0.05), reduce dead stock by 15%, and reduce operational costs by 10%. Conclusion: The Lean Management strategy significantly improved medication management efficiency in the hospital pharmacy. Recommendations for ongoing implementation and staff training are needed to maintain optimal results.